Record solar UV irradiance in the tropical Andes - Cabrol, Nathalie A.; Feister, Uwe; Häder, Donat-Peter; Piazena, Helmut; Grin, Edmond A.; Klein, Andreas (Frontiers in Environmental Science, 2014)
High elevation, thin ozone layer, and clear sky produce intense ultraviolet (UV) radiation in the tropical Andes. Recent models suggest that tropical stratospheric ozone will slightly decrease in the coming decades, potentially resulting in more UV anomalies. Data collected between 4300 and 5916 m above sea level (asl) in Bolivia show how this trend could dramatically impact surface solar irradiance. During 61 days, two Eldonet dosimeters recorded extreme UV-B irradiance equivalent to a UV index (UVI) of 43.3, which is the highest ground value ever reported. If they become more common, events of this magnitude may have societal and ecological implications, which make understanding the process leading to their generation critical. Our data show that this event and other major UV spikes were consistent with rising UV-B/UV-A ratios in the days to hours preceding the spikes, trajectories of negative ozone anomalies (NOAs), and radiative transfer modeling.